Variabel Dan Metadata Rekam Medis Elektronik Sebagai Standar Interoperabilitas Data Kesehatan di Rumah Sakit - Andriani, Rika; Pertiwi, Julia; Alfitasari, Arum; Salima, Tri Anita Restu; Wijayanti, Triya (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
Electronic Medical Records (EMRs) require interoperability capabilities to effectively integrate with other health information systems. For EMRs integration, it is crucial to adhere to the guidelines outlined in KMK HK.01.07/MENKES/1423/2022. The implementation of EMRs was carried out in 2019 at Hospital X. Until now, Hospital X has not adjusted the EMRs’ variables and metadata. This study aimed to analyze EMRs’ variables and metadata for health data interoperability. This was a quantitative study. Data collection used a documentation study guideline instrument. Data analysis used descriptive statistic. This study showed that variables and metadata from 5 datasets consisting of emergency, outpatient, inpatient, laboratory, and pharmacy datasets, there were 45,3% exist and appropriate; 20% exist and inappropriate, and 34,7% do not exist compared to KMK HK.01.07/MENKES/1423/2022. To improve the quality of EMRs, it is necessary to adjust variables and metadata in accordance with KMK HK.01.07/MENKES/1423/2022; identify users’ data and information needs; and conduct periodic quality audits and evaluations of EMRs.